Synthesis and cytotoxic effect of a few N-heteroaryl enamino amides and dihydropyrimidinethiones on AGS and MCF-7 human cancer cell lines - Tavangar, Sajjad (Res Pharm Sci, 2020)
BACKGROUND AND PURPOSE: Cancer prevalence has increased in the last century posing psychological, social, and economic consequences. Chemotherapy uses chemical molecules to control cancer. New studies have shown that dihydropyrimidinethione (DHPMT) derivatives have the potential of being developed into anticancer agents. EXPERIMENTAL APPROACH: New derivatives of DHPMTs and a few acyclic bioisosters were synthesized via Biginelli reaction and assessed for their toxicity against gastric (AGS) and breast cancer (MCF-7) cell lines through MTT method. FINDINGS / RESULTS: Chemical structures of all synthesized N-heteroaryl enamino amides and DHPMTs were confirmed by spectroscopic methods. Result of biological assessment exhibited that none of the tested agents was more cytotoxic than cis-platin against AGS and MCF-7 cell lines and compound 2b was the most cytotoxic agent against AGS (IC(50) 41.10 μM) and MCF-7 (IC(50) 75.69 μM). Cytotoxic data were mostly correlated with the number of H-bond donors within gastric and breast cancer cells. CONCLUSION AND IMPLICATIONS: It was realized that DHPMTs were able to inhibit the growth of cancer cells much better than acyclic enamino amides and moreover; N-(4-methylbenzothiazol-2-yl) DHPMT derivative (2b) supposed possible interaction with a poor electron site of target due to the lipophilic nature of benzothiazole ring and also less electron rich nature than isoxazole. Similar scenario was observed with acyclic enamino amides in which incorporation of sulfur and nitrogen containing heterocycles doubled the cytotoxic effects. Results of the present contribution might assist in extending the scope of DHPMTs as privileged medicinal scaffolds.